Symbols and Images of Antiquity and Christianity in Culture of Russian Society (on Results of Interuniversity Scientific-Practical Conference) - M. A. Vengranovich; I. V. Gurova (Научный диалог)
The results of the interuniversity scientific-practical conference in Povolzhsky Orthodox Institute (Tolyatti) are presented. It is reported that the forum discussed questions related to the comprehension of the historical experience of revolutions and the fall of the monarchy in the Russian society. Also the subject of discussion at the conference was the influence of Christianity and antiquity on the formation of religious-philosophical, moral, aesthetic and artistic principles of Russian and European cultures.